Herding Behaviour in Asutralian Stock Market: Evidence on Covid-19 Effect - Espinosa-Mendez, C (Routledge, 2021)
This is the first article in investigating how COVID-19 affects Oceania’s financial markets. Specifically, we investigate if COVID-19 pandemic has an effect on herding behaviour in the Australian stock market. Using a sample of all firms listed over the period from 10 June 2008 to 19 June 2020, we find evidence that COVID-19 pandemic increases herding behaviour. The results report that herding behaviour manifests during crisis and extreme periods. © 2020 Informa UK Limited, trading as Taylor & Francis Group.